Hegel’s Theory of Love as an Attitude to Life - Rózsa, Erzsébet (ETHICS IN PROGRESS, 2025)
For those who see Hegel as the philosopher of the closed system or the Prussian monarchy, it may come as a surprise or even a shock that love is one of the greatest and still inspiring topics of his philosophy. Hegel’s theory of love can enrich contemporary discussions on the philosophy of emotions and the theory of feeling in many ways, provided that it is reconstructed in a philologically and hermeneutically correct, philosophically profound and astute manner. The present paper will discuss Hegel’s views on love in two contexts. The first context is the history of progress summed up in his early considerations, which he treats in the field of tension between religion and philosophy. Within the extremely broad and manifold cultural horizon of the early works, Hegel assigns an existential meaning to love not only in an individual, but above all in an inter-individual sense. It is precisely in Hegel’s treatment of love that one can recognise the first germs of his intersubjective model of human existence – including individual existence – as it appears in his mature philosophy (second context).